THE EFFECTIVENESS OF JEROME BRUNER’S SCAFFOLDING METHOD IN IMPROVING SPEAKING SKILLS IN PRIMARY EDUCATION - Putri, Amelia; Prastiwi, Andini Eka; Hidayani, Selnistia (ADIBA : JOURNAL OF EDUCATION, 2024)
The basis The foundation for children's future language proficiency and overall academic success is established through teaching English to young learners (TEYL), which is a critical aspect of primary education. This study investigates the effectiveness of Jerome Bruner's scaffolding theory in enhancing the speaking skills of primary school students. Utilizing a quasi-experimental design with random sampling for pre-test and post-test assessments, the study employs a quantitative experimental methodology. The research focuses on key aspects of speaking skills: pronunciation, fluency, and accuracy. Conducted with 28 students from class 5A at SDN Karawaci Baru 2, the study applies scaffolding techniques during English language instruction to measure their impact. The results demonstrate significant improvements in the students' speaking abilities, with statistical analysis revealing a marked increase in pronunciation, fluency, and accuracy (p < 0.001). This study concludes that the scaffolding method is a valuable pedagogical approach for enhancing speaking skills in young English language learners.